PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TIMELINESS LAPORAN KEUANGAN (Media Riset Akuntansi, 2022)
The purpose of this study was to examine the effect of corporate governance mechanisms consisting of institutional ownership, independent commissioners, audit committees, KAP size and profitability on the timeliness of submitting the company's financial statements. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique used is the purposive sampling method. There are 192 samples of companies that meet the criteria as research samples. The analytical method used to test the hypothesis is logistic regression analysis. The results showed that the audit committee had a significant positive effect on the timeliness of submitting financial statements. The results of this study also found that independent commissioners have a negative effect on the timeliness of financial report submission. Meanwhile, institutional ownership, KAP size, and profitability have no effect on the timeliness of financial report submission.